Risk factors and public health interventions associated with adolescent pregnancy prevention among females aged 10–19 years in Kenya: a scoping review protocol - Abdu Mohiddin; Kimbley Asaso Omwodo; Danielle Denwood; Augustine Gitonga (BMJ Open)
Background Adolescent pregnancy is associated with multifaceted challenges that impact countries’ health, education and economic stability. Despite ongoing interventions, in developing countries such as Kenya, adolescent pregnancy rates continue to be high. There is a need for more synthesised evidence on regional-specific risk factors to support tailored prevention strategies.Objective This scoping review aims to explore what is known about the risk factors and intervention strategies focused on adolescent pregnancy prevention in Kenya.Methods and analysis Using the Arksey and O’Malley framework combined with a three-step search strategy as recommended by the Joanna Briggs Institute, relevant articles will be identified from the PubMed, Scopus, Web of Science, CINAHL and PsycINFO databases. The focus will be on literature published from 1 January 2008 to 31 December 2023, addressing risk factors and public health strategies aimed at adolescent pregnancy prevention in Kenya. The analysis will involve thematic data extraction and charting to highlight patterns in adolescent pregnancy risk factors, intervention outcomes and existing gaps.Ethics and dissemination No ethical approval is needed. The dissemination strategy includes peer-review publication and presentation to relevant stakeholders.Conclusion This review will provide a comprehensive summary of the literature on the risk contributors and interventions for adolescent pregnancy prevention in Kenya. The evidence map may be used by relevant stakeholders to address adolescent pregnancy prevention gaps in strategy as well as inform interventions that are context-specific.Registration Open Science Framework (https://doi.org/10.17605/OSF.IO/Q5F9G); Pre-results.